تحليل طرق تعليم اللغة العربية في الصف السابع المتوسط بمدرسة الدرة ميدان - Febrina, Dina; Karo, Tiy Kusmarrabi; Anhar, Khairul (ANWARUL, 2024)
The aim of this research is to know the method of teaching the Arabic language used in the seventh intermediate grade at Al-Durra Maidan School, as well as its advantages and disadvantages. The method used in this research is the descriptive qualitative method and the methods used to collect data are observation and interview. . The approaches are in a step-by-step method from Miles dan Huberman. The result of the research is that the methods of teaching the Arabic language in the seventh intermediate grade are the lecture method, the memorization method, the question training method, and the response method. The application of the teaching method in teaching the Arabic language in the seventh intermediate grade at Al-Durra Maidan School follows the same method according to the method. The advantages in all teaching methods support the learning process, and the disadvantages of all teaching methods are a factor that hinders the effectiveness of learning.